Upaya Peningkatan Kemampuan Guru Menggunakan Metode Pembelajaran melalui IHT - Endang Retnowati (Universitas Muria Kudus, 2020)
The teacher is the person most responsible for the quality and meaningfulness of the learning process in the classroom. Therefore, teacher performance is very influential on the success of a learning process. In connection with the teaching and learning process teachers should be able to direct and guide students to be active in teaching and learning activities so as to create a good interaction between teacher and students and students and students. Based on the above it should be in the teaching and learning process a teacher is able to choose and use appropriate learning methods, so students can learn effectively and efficiently according to the expected goals. then the teacher and researcher make an agreement to improve the existing conditions through IHT (In House Training) activities. From the results of the implementation of IHT in the initial study, cycle I, and cycle II, it has increased. The average value of students after using the Learning Method for class IV in the Initial Study of 1.83 increased to 2.55 in the first cycle and increased again to 3.67 in the second cycle. Then for class V, in the pre cycle get an average of 2.00 and in the first cycle to 2.67 and an increase in results in the second cycle reaches an average value of 3.67. and the last in class VI, getting an average value of 2.33 in the pre cycle, 2.67 in the first cycle and in the second cycle has increased to 3.50.